Critical Cross-Cultural Management: Outline and Emerging Contributions. Issue 4 (2nd October 2018) - Romani, Laurence; Mahadevan, Jasmin; Primecz, Henriett
Abstract : Abstract : Critical perspectives on cross-cultural management (CCM) are increasingly present in our research community; however, they are spread over multiple research fields (e.g., international business, International Human Resource Management (IHRM), diversity, and gender and/or race studies). Critical researchers tend to have agendas and foci that address topics others consider beyond CCM's scope, such as gender in intercultural training, religion in the multi-cultural workplace, or the relationship between CCM knowledge and the military. We intend to sketch here the contours of this stream of research we call critical CCM and to clarify the broadly shared research studies' agenda. By using Burrell and Morgan (1979 ) matrix and stressing critical studies' inspirations in two paradigms, radical structuralism and radical humanism, we propose a paradigmatic positioning of the studies. Subsequently, we articulate Critical CCM research agenda around denaturalization, reflexivity, and emancipation. We conclude by asserting a critical performative agenda in a dialog with practitioners. In brief, our ambition is to specifically outline Critical CCM research and show its emergent contribution to CCM research.